Analysis of Marketing Strategy in Efforts to Increase the Competitiveness of SMEs - Dedy Dwi Arseto; Anggraini Syahputri (Enrichment : Journal of Management, 2021)
Marketing strategy plays an important role in small, medium and micro businesses. The important role of the right marketing strategy will be able to increase the competitiveness of the products produced by MSMEs. Developing a marketing strategy requires complete information about the market, consumers and the products they need. The lack of understanding of MSME actors in using technology in the Industrial Revolution 4.0 era as a marketing strategy certainly makes it more difficult for SMEs to compete. The purpose of this study is to analyze the application of marketing strategies in an effort to increase the competitiveness of SMEs, to analyze the development of marketing strategies in an effort to increase the competitiveness of SMEs. The results of this study are the marketing strategy carried out by MSME actors in Tebing Tinggi City, it was found that 60% of MSME actors did not understand the use of the marketplace as a means of marketing products on a wider scale. This is due to the limited understanding of MSME actors and the product packaging and types of products being sold cannot sell through the marketplace. However, as many as 87% of MSME actors have used social media as a forum for market development and promotion. Utilizing technological developments as a means of promoting and selling strategic products on the SWOT matrix. MSME actors do not fully use and utilize the currently available technology to the fullest. Selling products through the marketplace and social media provides many advantages, especially the unlimited marketing area and being able to get a large number of consumers.